2012
DOI: 10.5539/sar.v1n2p188
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Fertilizer Policy, Farmers’ Perceptions and Implications for Future Agricultural Development in Nepal

Abstract: <p>This paper assesses the origins of and changes to fertilizer policy in Nepal over a period of time. It assesses farmers’ awareness of the recent changes to the subsidy policy and examines their perceptions of the extension services. This paper looks at the environmental implications of the concentrated application of chemical fertilizer, particularly as far as food security is concerned. Questionnaire surveys, group discussions, a workshop, soil analyses and archival materials were used to collect dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…While few other crops were found not cultivated in those areas due to the lack of manpower, market and economic benefit. In contrast, the adoption of various crops and use of agro-inputs in farming were influenced by infrastructural development together with adoption of GR in other studies (Brown and Shrestha, 2000;Brown and Kennedy, 2005;Raut et al, 2011;Raut et al, 2012). With introduction of higher yielding varieties of crops and vegetables, the traditional varieties of rice and maize are in process of disappearing with few of the varieties already non-existent from these regions.…”
Section: Discussionmentioning
confidence: 93%
“…While few other crops were found not cultivated in those areas due to the lack of manpower, market and economic benefit. In contrast, the adoption of various crops and use of agro-inputs in farming were influenced by infrastructural development together with adoption of GR in other studies (Brown and Shrestha, 2000;Brown and Kennedy, 2005;Raut et al, 2011;Raut et al, 2012). With introduction of higher yielding varieties of crops and vegetables, the traditional varieties of rice and maize are in process of disappearing with few of the varieties already non-existent from these regions.…”
Section: Discussionmentioning
confidence: 93%
“…Several studies also revealed that knowing the policy affects the practice of farmland transfer, which is in accordance with our results. For example, Raut and Sitaula [48] found that, when 12% of the farmers knew about a change in the fertilizer policy, 44% of those with that knowledge were willing to adjust their modes of agricultural production and operations. As Meng [47] observed, some farmers who received subsidies abandoned the opportunity to immigrate to cities.…”
Section: Discussionmentioning
confidence: 99%
“…Meng stated that the grain subsidy policy prevents farmers from leaving rural areas; therefore, more farmers are reluctant to conduct farmland outflow. Raut and Sitaula [48] examined the perception of fertilizer subsidy policy in Nepal based on data from a survey conducted in 1038 households. They stated that, although only a few farmers are aware of the changes in the subsidy policy, most of them are satisfied and would take action to expand production to make the policy effective.…”
Section: Policy Reformmentioning
confidence: 99%
“…Traditionally, many varieties of local vegetables, herbs, spices and other food crops and breeds of livestock were sustained on the forest resources and livestock compost. Some of the plant species are chemical fertilizer intolerant (Raut et al, 2012).…”
Section: The Importance Of Multipurpose Management Of Forests and Evomentioning
confidence: 99%
“…Crop varieties suitable in less productive and rain-fed land are disappearing from communities as farm manure production or availability decreased with the restrictions on forest use for livestock production and mobility. The land is either abandoned for cropping or put to other uses because of decreasing farm manure supplies and increasing fertilizer prices (Raut et al, 2012). Loss of vegetable species susceptible to fertilizer is natural in the shortage of farm manure as it happened in England in 1960s (Robinson & Sutherland, 2002).…”
Section: Biodiversity Lossmentioning
confidence: 99%